The Peer to Peer Social Fabric as a Platform for General Collective Intelligence - Williams, Andy (My University, 2020)
INTRODUCTION: General Collective Intelligence or GCI has been defined as a platform that combines individuals into a collective intelligence with the potential for exponentially greater general problem-solving ability (intelligence) than that of any individual in the group. Cognitive computing applications are executed by intelligent agents on a user’s behalf to optimize individual user outcomes. Cognitive computing platforms are executed by individuals organized by a GCI to achieve greater collective outcomes. The Peer to Peer Social Fabric (P2PSF) is an infrastructure platform proposed to enable the execution of cognitive computing applications or platforms. OBJECTIVES: To explore the functionality required by an infrastructure platform with the capacity to enable the operation of cognitive computing applications or platforms. And to determine whether the functionality of the proposed Peer to Peer Social Fabric is sufficient. METHODS: The requirements of collective cognitive computing were assessed, including the requirement to increase capacity for complexity, capacity to scale number of processes, and capacity to sustain processes. The proposed high-level specifications of the Peer to Peer Social Fabric were compared to those requirements to determine whether that functionality is sufficient. RESULTS: The proposed Peer to Peer Social Fabric appears to meet the requirements of both the operating system for GCI, as well as the requirements of a client enabling individuals and organizations to access either AGI or GCI functionality. CONCLUSION: All of the functionality required by he Peer to Peer Social Fabric might already exist, but an understanding of how that functionality must be combined in order to achieve the exponential increase in general problem-solving ability potentially possible through AGI or GCI is a new and important contribution.
Keywords: General Collective Intelligence; Human-Centric Functional Modelling; Artificial General Intelligence; Peer to Peer Social Fabric